Introducing Chaetothyriothecium, a new genus of Microthyriales - Hongsanan, Sinang; Chomnunti, Putarak; Crous, Pedro W.; Chukeatirote, Ekachai; Hyde, Kevin D. (Phytotaxa, 2014)
The order Microthyriales comprises foliar biotrophs, epiphytes, pathogens or saprobes that occur on plant leaves and stems. The order is relatively poorly known due to limited sampling and few in-depth studies. There is also a lack of phylogenetic data for these fungi, which form small black spots on plant host surfaces, but rarely cause any damage to the host. A "Microthyriaceae"-like fungus collected in central Thailand is described as a new genus, Chaetothyriothecium (type species Chaetothyriothecium elegans sp. nov.). Phylogenetic analyses of LSU gene data showed this species to cluster with other members of Microthyriales, where it is related to Microthyrium microscopicum the type of the order. The description of the new species is supplemented by DNA sequence data, which resolves its placement in the order. Little molecular data is available for this order, stressing the need for further collections and molecular data.